Penerapan Strategi PAKEM Dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Pendidikan Pancasila - Dwi Vikram; Agung Setyawan; Sih Widayati (Citra Dharma Cindekia, 2024)
This research aims to increase the learning motivation of fifth grade students in the Pancasila Education subject through the implementation of the PAKEM (Active, Creative, Effective and Fun Learning) learning strategy at SDN Tanjung Jati 2. The research method used is descriptive-qualitative, with data collection through observations and interviews. The research results show that the gradual implementation of the PAKEM strategy is able to increase the motivation of students who were initially passive to become more active and involved in the learning process. Teachers also experience increased creativity in teaching. With the PAKEM approach, the classroom atmosphere becomes more enjoyable, and students are more motivated in participating in Pancasila education learning.